1083 A REVIEW OF FAST DATA IN TALLAGHT UNIVERSITY HOSPITAL, AND THE IMPACT OF COVID ON TREATMENT. (14th June 2022) - O'Connor, A; Hobson, H; Collins, R
Abstract: Introduction: Stroke is a leading cause of morbidity. Current guidelines advise maximum of 4.5 hours post symptom onset for thrombolysis, and 24 hours for thrombectomy. (1) Delay between symptom onset and treatment is associated with an inferior outcome. Thrombolysis is available in 27 Irish centers. Average rate of thrombolysis is 11%. (3) Fewer than half of stroke patients arrived in hospital within three hours of symptom onset in 2019. (4) Median door-to-needle time is 48 minutes. Method: FAST calls in Tallaght University Hospital, from 2/7/19–1/7/21, were included in this analysis (n = 594). Results: 160 FAST calls took place pre-Covid (20/month), and 434 post-Covid (27.12/month). Time of symptom onset was recorded in 390 cases. Time patients last seen well was known in 185 cases, unknown time of onset in 19. After review by the stroke clinician, FAST imaging was obtained in 78% of cases (n = 464). Of these, 34 cases of FAST imaging were performed for inpatients. Average time from registration to CT was 35:24 minutes pre covid, and 45:52 minutes post. 9.7% of patients were thrombolysed. The median door-to-needle time was 41 minutes pre-Covid(n = 21, 2.625/month), and 54 minutes after (n = 37, 2.3/month). Thrombectomy was performed in 46 cases. 222 patients were diagnosed with an ischaemic stroke, 50 had TIA and 48 had haemorrhagic strokes. Other diagnoses included migraine (6.7%, n = 40), seizures (6.7%, n = 40) and Bells Palsy (3.7%, n = 22). 55% (n = 330) of cases were registered to ED with FAST call between the hours of 9 am-5 pm. 27% (n = 161) of cases occurred during the night shift. Conclusion: The median door-to-needle times were below national median pre-Covid, and longer post-pandemic, with an increase in the rate of presentation in the same time-frame. This report highlights the effect of the pandemic on time-critical patient interventions in stroke and the need to stratify services to respond to structural challenges.